The big questions : a short introduction to philosophy - Solomon, Robert C. 4 0 16; Higgins, Kathleen M.; 5 (Australia; Wadsworth, Cengage Learning, 2010)
An introduction to philosophy that explains the central concerns of significant philosophers throughout history, covering the meaning of life, God, reality, truth, self, freedom, morality, justice, and beauty, as well as philosophy's connections with gender, race, and culture; and provides discussion questions at the beginning and end of each chapter.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Philosophy. -- 20; 20; 2